Fluid therapy response in endurance horses with metabolic ailments - Kuan, Kit Leng (2015)
Endurance riding is a fast-growing FEI discipline worldwide. Metabolically-eliminated endurance horses generally necessitate provision of fluid therapy. This study evaluates the physical, haematological and biochemical changes of metabolically eliminated endurance horses in response to fluid therapy. This study also determines the correlation of riding speed and distance travelled with abnormalities in physical, haematological and biochemical parameters that constitute metabolic elimination. Nine out of sixty-one endurance horses participating in an endurance ride were metabolically eliminated and sent to RTES/UPM Equine Hospital. These horses were examined by veterinarians and intravenous fluid therapy was indicated with 0.9% saline solution at rate of 5-10L hr-1. Blood sampling via jugular venipuncture was performed before and after fluid therapy. Heart rate, skin tenting duration, colour of mucous membrane, capillary refill time and gastrointestinal sounds improved significantly following fluid therapy. Haematological and biochemical parameters were consistent with haemodilution but several were restored back to normal reference values. In conclusion, there was significant difference in physical, hematological and biochemical parameters following intravenous fluid therapy. Since endurance horses with metabolic ailments in this study responded well to intravenous fluid therapy (0.9% saline solution), their prognosis was good. However, there was no significant correlation between riding speed with physical, haematological and biochemical parameters except for distance travelled with icterus index, bilirubin and urea.